Protecting Non-personal Data in the Framework of the Legislation of the European Union - Mustila, Ville (My University, 2020)
Data has become one of the most valued resources in today’s economy. With the introduction of Big Data analytics and the Internet of Things, it is vital for businesses of all sizes to gain access and benefit from non-personal data. While personal data is governed by the GDPR, non-personal data does not currently have any catch-all regulation within the EU. The majority of protection is brought by a combination of contract law and technological means. This Master’s thesis aims to explore the current EU legislation in order to determine whether or not there are ways to protect non-personal data within the EU, and how this protection could be developed. The thesis is mostly legal dogmatic in nature, but some comparative and critical legal perspectives are also taken. Additionally, some technological terminology and economic theories of value are used. Conclusion is that some EU legislation, namely the Database Directive and the Trade Secrets Directive could offer protection to non-personal data that falls within their scope. This, however, is not necessarily a very significant portion of the data. In the U.S. trade secrets protection, the civil law regulations seem to be even stricter on what can benefit from trade secrets protection. Data ownership and non-legislative measures are explored as possible avenues forward, but in the end, there are benefits to both legislating and using non-binding measures. It is concluded that the best solution would likely involve a combination of both, in addition to the development of technical means of protection. Further research in the area is required.

Datasta on tullut yksi taloutemme ja yhteiskuntamme tärkeimmistä resursseista. Big Datan ja esineiden internetin (Internet of Things) vallankumouksen myötä Big Data analytiikasta on tullut tärkeää myös sellaisille yrityksille, joiden liiketoiminta ei suoraan liity dataan. Vaikka EU:n alueella Tietosuojaasetus säänteleekin henkilötietoja hyvin pitkälle, ei muun tyyppisiä tietoja koskevaa sääntelyä ole juuri lainkaan. Tämän pro gradu -tutkielman tarkoituksena on kartoittaa EU:n nykyisen lainsäädännön sisältöä, sekä arvioida miten sitä voisi hyödyntää yritysten dataomaisuuden suojelussa. Lisäksi se tutkii mahdollisuuksia lainsäädännön kehittämiseksi tällä alueella. Tutkielman metodi on pitkälti oikeusdogmaattinen, vaikkakin jonkin verran oikeusvertailua ja oikeuskriittistäkin näkökulmaa on hyödynnetty. Myös teknologista termistöä ja taloustieteen arvoteorioita käytetään hyödyksi. Tutkielman tulosten perusteella voidaan todeta, että sekä EU:n Tietokantadirektiivi, että Liikesalaisuusdirektiivi voivat olla hyödyksi datan suojelemisessa. Direktiivien asettamien vaatimusten vuoksi niiden kattavuus jättää kuitenkin toivomisen varaa, eikä Yhdysvaltojenkaan liikesalaisuuslainsäädännön tarkastelu tuottanut laajempaa tulosta. Toimivin tulevaisuuden ratkaisu datalainsäädännön alalla tulee todennäköisesti olemaan jonkinlainen yhdistelmä datan omistajanoikeuksia, ei-lainsäädännöllisiä keinoja ja teknologisten suojausmuotojen kehittämistä. Selkeiden vastausten saamiseksi tarvitaan lisää tutkimusta.
Keywords: EU law, non-personal data, trade secrets, data rights, Internet of Things, Big Data, data, liikesalaisuudet, EU-oikeus, muut kuin henkilötiedot, teollisuusdata, datan määrittely